Lunch with Sonny. IN Reveille [column] - Farolan, Ramon J. (2017)
The author shares a what he knows about Senator Sonny Trillanes IV and the matters they talked about in a lunch with a small group of friends.
Keywords: Trillanes, Antonio F., IV